Annual yield potential of grain sorghum under irrigated conditions - Aguiar, Paulo Anselmo Andrade (Pesquisa Agropecuaria Brasileira, 2014)
The annual sorghum (Sorghum bicolor L. Moench) grain production potential of eight commercial hybrids and two varieties was evaluated under irrigated conditions in the São Francisco Valley. A double row system spaced 40 cm apart in beds of 70 cm width, with approximatelly 15 plants/m in each row. The hybrids tested were much more productive than the varieties. A gradual decrease in the average yield was obtained from the first harvest to the first and second ratoon cropping, with 9,313, 6,476 and 3,602 kg/ha, respectively. The total average yield from the three harvests reached 19,391 kg/ha which indicates the technical viability of exploring grain sorghum under irrigated conditions.